Municipal economic law: the “economic constitution” in Pouso Alegre, Minas Gerais - Teixeira Gonçalves, Gustavo (Universidad Nacional del Litoral, 2019)
This paper aims to analyze the economic order as put forward by the 1988 Federal Constitution under the ideological and practical perspective of an Economic Constitution. The main goal is to verify if the Organic Law of the Pouso Alegre city, Minas Gerais state, in establishing rules regarding the local business activities, followed the framework of the Magna Carta, in particular if it incorporated the standards of an Economic Constitution. This paper shows its relevance in regard on the active role the local public power plays within the boundaries of the economic relations that happens within city limits. The paper is the product of a bibliographic research aimed to comprehend the Economic Constitution, focusing the analyses on the 1988 Constitution and the Organic Law of the Pouso Alegre city.